Correlation of Advanced Glycation Endproducts Estimated From Skin Fluorescence in First-Degree Relatives: The Impact of Adjustment for Skin Pigmentation. (18th November 2014) - Báez, Eileen A.; Shah, Shreepal; Felipe, Dania; Maynard, John; Chalew, Stuart
Objective: The objective was to assess the relationship of skin advanced glycation endproducts (AGEs) between first-degree relatives estimated from skin fluorescence (SF) after adjustment for skin pigmentation. Study design: SF was excited by LEDs centered at 375, 405, and 420 nm from children with type 1 diabetes and their mothers. Data were adjusted to generate measures of skin intrinsic fluorescence (SIF) at the various excitation wavelengths, using 2 different pairs of correction coefficients for excitation (kx) and emission (km): kx = 0.5, km = 0.5 (not associated with skin pigmentation) and kx = 1.0, km = 0.0 (strongly associated with skin pigmentation). Pearson correlation analysis was performed, as well as a multiple variable analysis with maternal SIF adjusted for the effects of maternal age and race. Results: There were 50 matched pairs of children and their mothers. Children were 13.3 ± 3.7 years of age and there were 19 boys/31 girls and 15 black/35 white. Mothers were 41.8 ± 6.8 years of age. The age of mother and child was highly correlated, r = .64, P < .0001. In Pearson correlation analysis, child's SIF (kx = 1.0, km = 0.0) the had strongest association with maternal SIF, while with SIF (kx = 0.5, km = 0.5) there was a trend for association. In the multiple variable model child SIF was associated with maternal SIF for all corrections and wavelengths but was stronger for kx = 1.0, km = 0.0. Conclusion: Even after adjustment for skin pigmentation and race, correlation of SIF between family members persists, suggesting that other genetic and/or environmental factors shared by parent and child may influence estimated skin AGEs.